Treatment‐Related Mortality With Everolimus in Cancer Patients. (2nd May 2014) - Wesolowski, Robert; Abdel‐Rasoul, Mahmoud; Lustberg, Maryam; Paskell, Maria; Shapiro, Charles L.; Macrae, Erin R.
Abstract : Introduction: The overall incidence and odds of fatal adverse events (FAEs) after exposure to everolimus are not well defined. We performed a comprehensive meta‐analysis of published randomized controlled trials (RCTs) to determine the role of everolimus in treatment‐related mortality in patients with cancer. Methods: PubMed databases and abstracts from the proceedings of the American Society of Clinical Oncology and the San Antonio Breast Cancer Symposium were searched for RCTs of everolimus either alone or in combination with another agent compared with the control arm without everolimus and that reported deaths from an adverse event from January 1966 to July 2013. The primary objective was to determine the difference of FAEs between everolimus‐treated patients and control group patients. Results: In total, 2, 997 patients with multiple solid tumors from nine RCTs were included. The overall incidence of FAEs in cancer patients treated with everolimus was 0.7% (95% CI 0.3%–1.1%) compared with 0.4% (95% CI 0.0%–0.7%) in cancer patients who did not receive everolimus. The odds ratio of FAEs was greater in everolimus‐treated patients (Peto odds ratio = 3.80, 95% CI 1.59–9.07, p = .003). In subgroup analyses, no significant difference was found in the incidence or odds of FAEs by everolimus administration (alone or in combination) or tumor type (breast cancer vs. nonbreast cancer; p = .63). Conclusion: In patients with cancer, everolimus is associated with a small but significant increase in the odds of a treatment‐related fatal events. Abstract : This meta‐analysis reviewed randomized clinical trials of everolimus alone or in combination versus placebo or control treatment in patients with solid tumors. It found a small but statistically significant increase in fatal adverse events among everolimus‐treated patients. Oncologists should select patients carefully for this therapy and should monitor and rapidly manage everolimus‐related toxicities.